Retrospective evaluation of traction time for impacted dilacerated maxillary central incisors in mixed dentition - ŞEN YAVUZ, BETÜL; YILMAZ, MÜESSER AHU; HAZNEDAROĞLU, EDA; UĞURLU, FAYSAL; MENTEŞ, ALİ RECAİ (My University, 2023)
PurposesThis study aimed to contribute to understanding the factors affecting the time of traction treatment of impacted dilacerated maxillary central incisors.MethodsThis retrospective study included children aged 8 – 11 years with a history of trauma, who applied to the pediatric dentistry clinics of Marmara University, School of Dentistry, between December 2013 and December 2019, and were treated for unilateral impacted dilacerated maxillary upper central incisors. Children\"s age, sex, digital panoramic radiographs, cone-beam computed tomography, and intraoral photographs were retrieved from electronic dental health records. The effects of children\"s age, sex, the direction of impacted teeth, distance of the teeth to the top of the alveolar crest, and root dilaceration level on traction time were analyzed by Mann-Whitney U test and Spearman\"s rank correlation coefficient test.ResultsThe inverse position of the incisors significantly increased the traction time (P = 0.012). However, the traction time did not differ according to the sex of the children (P = 0.707) or the level of root dilaceration (P = 0.429). No correlation was observed between the traction time and the age of children (P = 0.644) or the distance of the incisors from the top of the alveolar crest (P = 0.397).ConclusionsIn cases of the forced eruption of for the impacted dilacerated maxillary central incisors, the direction of the teeth should be evaluated when deciding on the treatment plan, as it may affect the treatment time.
Keywords: Diş Hekimliği; Klinik Bilimler; Pedodonti; Sağlık Bilimleri; Dentistry; Clinical Sciences; Pedodontics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry